siRNA therapeutics for effective management of rheumatoid arthritis - Vishakha R. Chakole; Tathagata Dutta; Priyankar Sen (Next Nanotechnology)
siRNA is a specialized type of RNA that precisely targets a mRNA, and effectively silences the respective genes. This property makes siRNA a valuable tool for developing RNAi therapeutics, particularly for managing conditions like osteoporosis, cancer, genetic disorders, and autoimmune disorders. Rheumatoid arthritis (RA) is a significant autoimmune disorder. Several treatments are available for RA, including analgesics, corticosteroids, DMARDs, biological agents, combinational therapy, epigenetic and cell therapies which play a crucial role in preventing joint function deterioration, inflammation, synovial edema, etc. Besides these numerous advantages, these treatments have several disadvantages like liver cirrhosis, interstitial lung disease, sexual health is impaired in males, neuropsychiatric adverse effects, etc. All these disadvantages engender the need for new therapy. siRNA delivery carriers like liposomes, polymeric nanoparticles, and siRNA polymer bio-conjugates are proving to be particularly effective with less toxicity compared to the traditional treatments. A promising addition to these carriers is wrapsome (WS), which can be used as a favorable carrier for delivery of siRNA to its specific sites, such as inflamed joints or the inflamed synovium. The incorporation of PEG liposomes in the delivery strategy allows WS to evade recognition by the RES, leading to an extended half-life. This extended half-life enables a sustained, slow release of the drug, contributing to superior recovery from pain and inflammation associated with conditions like RA.